Performing participation? The Norwegian planning & building act and its understanding of citizen participation - Ringholm, Toril; Nyseth, Torill; Hanssen, Gro Sandkjær (AESOP, 2016)
Since 1985, the Norwegian Planning and Building Act has encouraged and required citizen participation at an early stage of the planning process. The argument lies in the advantage of opinions and concerns being identified as early as possible, avoiding the process coming to a standstill because vital points of view were presented too late in the process. Over the years, a neo-liberal planning practice has emerged, particularly in zoning planning, allowing private business actors into the early phases of the process – earlier than used to be the case. This does not mean that the ambitions with regard to the inclusion of citizens have been reduced. Rather the opposite. In the new P&B Act, from 2008 participation is emphasized even further, and now with a particular focus on including social groups that needs special attention. At the same time, the new P &B. Act also strengthened its focus on efficiency, and thereby institutionalize the the tension between democracy and efficiency (Holsen, 2000). Studies of planning practices in Norwegian municipalities find all forms of negotiations, mediation activities and consultations in planning processes. However, the most common practice is the minimum requirements in the law, which is announcing start-up of the planning process, and public hearing of the planning proposal. The studies also demonstrate that the attention is often directed towards other public agencies and businesses, and less towards citizen participation. Municipal planners find it difficult to involve citizens, due to lack of time, resources and awareness.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south